2017
DOI: 10.2147/cmar.s126136
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma in Niger Delta, Nigeria: complications and the outcome of palliative interventions

Abstract: BackgroundMultiple myeloma (MM) is one of the hematological malignancies that require palliative care. This is because of the life-threatening nature and the suffering associated with the illness. The aim of this study is to bring to the fore the complications experienced by people living with MM in the Niger-Delta region of Nigeria and the outcome of various palliative interventions.MethodsThis was a 10-year multi-center retrospective study of 26 patients diagnosed and managed in three major centers in the Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
3
17
1
Order By: Relevance
“…In terms of prognosis, the majority of our patients were classified at stage III of the ISS (78.8%). A study published in 2017 by Nwabuko, et al showed the predominance of stage III of the ISS [11]. Our results were different from the European series which reported stage I with a proportion of 32% [17][18][19].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In terms of prognosis, the majority of our patients were classified at stage III of the ISS (78.8%). A study published in 2017 by Nwabuko, et al showed the predominance of stage III of the ISS [11]. Our results were different from the European series which reported stage I with a proportion of 32% [17][18][19].…”
Section: Discussioncontrasting
confidence: 93%
“…The deterioration of the general state and bone pain were mainly observed as symptom in respectively 63.3% and 48.5%. These symptoms were found in the Nigerian and Central African studies [11][12][13][14]. This finding was related to the delay of diagnosis of our patients because of low financial means but also the accessibility to a consultation center so that most of our patients are seen late most often at the stage of complications.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This finding is similar to that reported by recently in Cameroon in the same hospital by Doualla-Bija, et al [14]. Several studies in Nigeria [6,13,15,18] and in the western world by Talamo, et al [12]. The pattern of presentation in our study clearly depicts late presentation as most of the patients presented with one or more complications.…”
Section: Discussionsupporting
confidence: 92%
“…It is the most common hematologic malignancy among blacks [3,4]. The aetiology of MM remains largely unknown [5], however, recent studies have identified the following factors implicated as potential risk factors of MM, increasing age (>65 years), male gender, black race, positive family history of MM or LHC (genetic influence), and monoclonal gammopathy of undetermined significance (MGUS) [6,7]. MM is usually preceded by a MGUS at a progression rate of 1% per year [8].…”
Section: Introductionmentioning
confidence: 99%